Fortune's daughter - Hoffmann, Alice 1951- (Putnam, 1985)
This tale of faith and love charts the histories of Rae, an unmarried expectant mother far from home, and Lila, a cynical fortune teller who lost her daughter twenty-five years earlier.
Keywords: Female friendship -- Fiction; Fortune tellers -- Fiction; Pregnant women -- Fiction; California -- Fiction; Psychological fiction